Scalability of digital psychological innovations for refugees: A comparative analysis in Egypt, Germany, and Sweden - Aniek Woodward; Sebastian Burchert; Alexandra S. Barry; Jacqueline E.W. Broerse; Egbert Sondorp; Anoushka Bold; Alexander Ruberl; Jonas M. Hessling; Christine Knaevelsrud; Bayard Roberts; Daniela C. Fuhr; Peter Ventevogel; et al. (Elsevier, 2023)
E-mental health interventions may offer innovative means to increase access to psychological support and improve the mental health of refugees. However, there is limited knowledge about how these innovations can be scaled up and integrated sustainably into routine services. This study examined the scalability of a digital psychological intervention called Step-by-Step (SbS) for refugees in Egypt, Germany, and Sweden. We conducted semi-structured interviews (n = 88) with Syrian refugees, and experts in SbS or refugee' mental health systems in the three countries. Data collection and analysis were guided by a system innovation perspective. Interviewees identified three contextual factors that influenced scalability of SbS in each country: increasing use of e-health, the COVID-19 pandemic, and political instability. Nine factors lay at the interface between the innovation and potential delivery systems, and these were categorised by culture (ways of thinking), structure (ways of organising), and practice (ways of doing). Factors related to culture included: perceived need and acceptability of the innovation. Acceptability was influenced by mental health stigma and awareness, digital trust, perceived novelty of self-help interventions, and attitudes towards non-specialist (e-helper) support. Factors related to structure included financing, regulations, accessibility, competencies of e-helpers, and quality control. Factors related to practice were barriers in the initial and continued engagement of end-users. Many actors with a potential stake in the integration of SbS across the three countries were identified, with nineteen stakeholders deemed most powerful. Several context-specific integration scenarios were developed, which need to be tested. We conclude that integrating novel e-mental health interventions for refugees into routine services will be a complex task due to the many interrelated factors and actors involved. Multi-stakeholder collaboration, including the involvement of end-users, will be essential.